2016
DOI: 10.3906/vet-1507-70
|View full text |Cite
|
Sign up to set email alerts
|

Presence of carbohydrate-digesting enzymes throughout the digestive tract of sheep

Abstract: IntroductionSheep breeding is one of the oldest professions closely associated with human civilization. The group of livestock called ruminants has a great utility. Sheep breeding yields meat and lambs, and, to a lesser degree, milk, wool, and hide. The physiology and morphology of sheep reflect adaptations to particular ecological niches. Based on food preference, sheep are herbivorous animals that prefer food rich in cellulose, i.e. 'grass/roughage eaters' (1). The most important feature of ruminants is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…With the exception of a single article focused on cellulolytic activity [29], the existing literature lacks information on the degradation parameters of food carbohydrates for roe deer. The methods applied here for measuring hydrolytic activities were those previously employed in our studies on sheep [25]. A comparison between these animals indicated that sheep digested all carbohydrates to a higher extent, with the exception of pectin, which was digested at a comparable level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of a single article focused on cellulolytic activity [29], the existing literature lacks information on the degradation parameters of food carbohydrates for roe deer. The methods applied here for measuring hydrolytic activities were those previously employed in our studies on sheep [25]. A comparison between these animals indicated that sheep digested all carbohydrates to a higher extent, with the exception of pectin, which was digested at a comparable level.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the hydrolytic activity of rumen samples, an enzymatic fraction was extracted using the carbon tetrachloride and lysozyme method as described by Miltko et al [25]. The resulting enzymatic fraction was used to determine the digestion rate of storage compounds (starch and inulin) and structural carbohydrates (xylan, cellulose and pectin), according to Miltko et al [25]. The reaction mixture contained substrate (solutions or suspensions of one of the following carbohydrates: starch, inulin, xylan, carboxymethyl cellulose or pectin); enzymatic fraction; and 0.01 M phosphate buffer (pH 6.0).…”
Section: Measurement Of Hydrolytic Activitymentioning
confidence: 99%
“…The mean values of the Eh detected in cecum of beaver varied from −237 to −259 mV, and were lower in comparison to the value of Eh found in cecum of rabbits. The low Eh value is necessary to obtain optimal conditions for development of anaerobic population of microorganisms (Michelland et al, 2010) and intensive digestive as well as fermentation processes (Miltko et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Po tym czasie, w celu zatrzymania reakcji, dodano kwas 3,5-dwunitrosalicylowy i próby inkubowano w temperaturze 100°C przez 5 minut. Szybkość trawienia węglowodanów -skrobi, pektyny, celulozy i ksylanu przez frakcję enzymatyczną treści żwacza oznaczono jako ilość uwolnionych cukrów redukujących podczas inkubacji (8). Ilość tych cukrów oznaczono spektrofotometrycznie przy długości fali 560 nm.…”
Section: Materiał I Metodyunclassified